AB0339 Safety of 23-Valent Pneumococcal Vaccine in Rheumatoid Arthritis Patients (Preliminary Results). (10th June 2014) - Naumtseva, M.S.; Belov, B.S.; Tarasova, G.M.; Karateev, D.E.; Luchikina, E.; Muravyev, Y.; Alexandrova, E.; Novikov, A.
Abstract : Background: Comorbid infections have significant impact on morbidity and mortality, especially in autoimmune rheumatic diseases. Therefore, prevention of infection is an integral part of supervision of these patients. Objectives: Safety study of 23-valent pneumococcal vaccine for patients with rheumatoid arthritis (RA), receiving therapy with disease modifying anti rheumatic drugs (DMARDs), and biological disease-modifying antirheumatic drugs (bDMARDs). Methods: The research included 72 people (women - 57 men - 15, at the age of 24 to 73 years), including 39 RA patients and 33 control subjects with a history of near ≥2 cases of lower respiratory tract infections (bronchitis, pneumonia). 24 patients with RA receiving methotrexate (MTX), 6 – leflunomide, 9 - tumor necrosis factor alpha (TNF-α) + MTX. 23-valent pneumococcal vaccine at 1 dose (0.5 ml) were injected subcutaneous continued MTX/leflunomide or 28-30 days before use TNF-α. Length of observation period after vaccination was 12 months. Results: In 49 cases (69% of observations) patients tolerated the vaccine without complications. In 19 cases (26%) pain, swelling and redness of the skin with a diameter of 2 cm was observed. In 4 cases (5%) the injection of vaccine resulted in low-grade fever. These reactions were not associated with the on-going antirheumatic therapy and they did not require changes in the treatment scheme. These reactions were fully resolved within 24 hours without additional treatment. Clinical and radiographic signs of pneumonia were not observed in any of the cases. Episodes of exacerbation of RA or the occurrence of any new autoimmune disorders during follow-up were not observed as well. Conclusions: Thus, preliminary results indicate sufficient clinical efficacy and good tolerability of the 23-valent pneumococcal vaccine for the patients with RA. For a more complete assessment of the effectiveness and safety of vaccine further clinical studies are recommended. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1248